2021
DOI: 10.4103/ijn.ijn_151_20
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia for pediatric arteriovenous fistula cannulation in hemodialytic patients: A comparison of lidocaine gel, lidocaine spray, and needle plate

Abstract: Background: Children undergoing hemodialysis (HD) via arteriovenous fistula (AVF) experience approximately 300 painful punctures per year which may lead to non-compliance with HD. This study was conducted to show the effect of local anesthetics on pain perception in AVF cannulation. Methods: This randomized clinical trial included 20 children under HD via AVF in Sheikh Children's Hospital Hemodialysis Center in February 2014. The first intervention was conducted as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…There are several reports in case of iatrogenic vascular injury during uterine curettage or surgical trauma that are classified as arteriovenous malformations (AVMs), arteriovenous fistulas, direct vessel ruptures, and pseudoaneurysms. 8 , 9 An arterial pseudoaneurysm is the formation of a periarterial bloody cyst that communicates with the arterial lumen through a narrow neck. It seems that pseudoaneurysms are more infrequent than other injuries.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports in case of iatrogenic vascular injury during uterine curettage or surgical trauma that are classified as arteriovenous malformations (AVMs), arteriovenous fistulas, direct vessel ruptures, and pseudoaneurysms. 8 , 9 An arterial pseudoaneurysm is the formation of a periarterial bloody cyst that communicates with the arterial lumen through a narrow neck. It seems that pseudoaneurysms are more infrequent than other injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine is a local anesthetic drug with a moderate effect and a short onset of action, which blocks the transmission of nerve messages in acute and chronic pain by inhibiting voltage-dependent sodium ion channels [11]. In this regard, the results of Ravanshad et al showed that the use of lidocaine gel has been associated with a reduction in pain during hemodialysis venipuncture in children [12]. A meta-analysis by Ghojazadeh et al showed the controversial effect of using topical lidocaine gel in reducing the pain caused by venipuncture [11].…”
Section: Extended Abstractmentioning
confidence: 99%
“…Research shows that 5.3% and 22% of adults have a severe and moderate fear of needles, respectively [ 5 ]. Nearly two million patients worldwide are dialysis-dependent, and of these, approximately 90% receive hemodialysis (HD) three times weekly [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HD is the most frequently used renal replacement therapy, and an arteriovenous fistula (AVF) is the gold standard for vascular access in these patients [ 6 ]. It is true for HD patients who experience a large-diameter needle insertion in the fistula area two to three times a week and about 300 times a year [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation